Pregnancy, Incantations, and Talismans in Early Medieval Japan: Chinese Influences on the Ritual Activities of Court Physicians - Alessandro Poletto (MDPI AG, 2021)
Court physicians (ishi or kusushi 医師), officials in the Bureau of Medications, were responsible for the well-being of court aristocracy since the establishment of a centralized state on the Japanese archipelago in the eighth century. Despite an increasing interest in the therapeutic arena of premodern Japan, scholars have tended to emphasize an epistemic divide between physicians and technicians employing other healing modalities, such as Buddhist monks and onmyōji 陰陽師, so that the former would be concerned with the physical body while the latter would not. However, this study focuses on the ritual and hemerological dimensions of the activities of court physicians within the crucial context of pregnancy and childbirth. By the twelfth century, court physicians affixed land-leasing talismans (shakuchimon 借地文) in the birthing room, pacified the birthing bed through incantations, and partook in the adjudication of a pregnancy-related hemerological notion known as hanshi (Ch: fanzhi). These practices appear in Ishinpō 医心方, which is a compendium of Chinese classics on therapeutics, hygiene, divination, and ritual that was compiled by Tanba no Yasuyori and presented to the court in 984. Ishinpō incorporates elements from multiple continental traditions, and some of the ritual practices discussed in this paper have at times been framed as “Daoist”. Since Daoist texts and institutions were never systematically brought or established in Japan, this study will rather stress the necessity of examining how Chinese textual traditions and ritual regimes were transmitted and distributed among institutions and technical groups within the Japanese state, in particular physicians from the Bureau of Medications and onmyōji from the Bureau of Yin and Yang.